2016
DOI: 10.1016/j.ajpath.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Healthy and Osteoarthritic Synovial Fibroblasts Produce a Disintegrin and Metalloproteinase with Thrombospondin Motifs 4, 5, 7, and 12

Abstract: Current description of osteoarthritis includes the involvement of synovial inflammation. Studies contributing to understanding the mechanisms of cross-talk and feedback among the joint tissues could be relevant to the development of therapies that block disease progression. During osteoarthritis, synovial fibroblasts exposed to anomalous mechanical forces and an inflammatory microenvironment release factors such as a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) metalloproteinases that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 66 publications
3
42
0
Order By: Relevance
“…Besides, ERK inhibitor decreased ADAMTS-12 mRNA and protein exclusively in OA-SF. Conclusions: We reported that ADAMTS-7 protein expression is higher in OA-SF compared to HD confirming previous data at mRNA level (1). As DKK decreased ADAMTS-7, Wnt-β-catenin signaling seems to be implicated in its expression.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Besides, ERK inhibitor decreased ADAMTS-12 mRNA and protein exclusively in OA-SF. Conclusions: We reported that ADAMTS-7 protein expression is higher in OA-SF compared to HD confirming previous data at mRNA level (1). As DKK decreased ADAMTS-7, Wnt-β-catenin signaling seems to be implicated in its expression.…”
supporting
confidence: 89%
“…As Runx2 and β-catenin are two transcription factors involved in chondrocytes metabolism and OA pathology (2-5), we studied whether these factors are implicated in the production of ADAMTS-7 and 12 in SF. Moreover, we analyzed the induction by two inflammatory mediators present in OA joints: interleukin-1β (IL-1β), and fibronectin fragments (Fn-fs), previously described in ADAMTS expression (1). Objectives: To elucidate the signaling pathways involved in the production of ADAMTS-7 and -12 in healthy donors (HD) -and OA-SF.…”
mentioning
confidence: 99%
“…Some studies consider ADAMTS4 the main factor implicated in OA because its levels are increased in the cartilage of these patients, correlating with a greater degradation of this tissue. However, other authors reported ADAMTS4 and -5 expressions in cartilage and SF, where ADAMTS5 was more expressed in SF from healthy donors (HD) than in OA, while ADAMTS4 gene expression was similar in both [33,50]. In addition, in vitro studies have shown that ADAMT5 activity is higher than that of ADAMTS4 [142].…”
Section: Aggrecanases and Proteoglycanasesmentioning
confidence: 96%
“…In this way, they are able to activate different signaling pathways such as the MAPK pathway or transcription factors such as NF-κB or AP-1 [9,[27][28][29][30][31]. In addition, they are able to establish a positive feedback with the Wnt/β-catenin pathway through integrins and MAPK signaling [32,33].…”
Section: Fibronectin Fragmentsmentioning
confidence: 99%
“…Our results demonstrate that KLF2 inhibits type Ⅱ collagen by suppressing the expression of MMP-13, suggesting the potential role of KLF2 in the treatment of OA. In addition to MMPs, aggrecanases and other catabolic enzymes have been considered to play an important role in the extracellular matrix, both directly and indirectly [27, 28]. Investigations of the effects of KLF2 on the activity of these enzymes are ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 99%